ESCLEREDEMA, CAUSA RARA DE MACROGLOSSIA - Monteiro, Marta; André, Carla; Santos, Mário; Goulão, João; Marta Pimentel, João (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2006)
.